Is superolateral Hoffa's fat pad hyperintensity a marker of local patellofemoral joint disease? – The MOST study. Issue 9 (September 2017) - Jarraya, M.; Guermazi, A.; Felson, D.T.; Roemer, F.W.; Nevitt, M.C.; Torner, J.; Lewis, C.E.; Stefanik, J.J.
Summary: Purpose: To determine the relation of superolateral Hoffa's fat pad (SHFP) hyperintensity to cartilage damage and bone marrow lesions (BMLs) in the patellofemoral joint (PFJ) and tibiofemoral joint (TFJ). Methods: We used data from the 60 and 84-month study visits from the Multicenter Osteoarthritis (MOST) study. SHFP hyperintensity and Hoffa-synovitis were graded from 0 to 3. Cartilage damage and BMLs were scored in the PFJ and TFJ. Structural damage was defined as: any cartilage damage, full-thickness cartilage damage and any BML. Worsening structural damage was defined as any increase in cartilage and BML scores. Logistic regression was used to determine the relation of SHFP hyperintensity and Hoffa-synovitis (>0) to structural damage, adjusting for age, sex and body mass index (BMI). Results: 1, 094 knees were included in the study. Compared to knees without SHFP hyperintensity, those with SHFP hyperintensity had 1.2 (95% Confidence Interval (CI), 1.1–1.4), 1.7 (1.3–2.3) and 1.6 (1.3–1.9) times the prevalence of any cartilage damage, full-thickness cartilage damage, and BMLs in the lateral PFJ respectively, and 1.1 (1.0–1.2), 1.3 (1.0–1.8), and 1.2 (1.0–1.4) times the prevalence of any cartilage damage, full-thickness cartilage damage, and BMLs in the medial PFJ. SHFP hyperintensity was associated with worsening BMLs in the medial PFJ (RR: 1.4 (1.0–1.9)). In general, there was no relation between SHFP hyperintensity and TFJ outcomes. Hoffa-synovitis was associated both cross-sectionally and longitudinally with structural damage, regardless of definition, in all compartments. Conclusion: SHFP hyperintensity may be a local marker of PFJ structural damage.